Strong-field ionization of the triplet ground state of O2 - Wangjam, Tomthin Nganba; Lam, Huynh Van Sa; Kumarappan, Vinod (My University, 2021)
Using strong-field ionization as a probe, we observe highly nonperiodic evolution of the spin-rotation wave packet launched by a nonionizing femtosecond pulse in oxygen. The nonperiodicity is readily apparent only in rotationally cold molecules that are pumped with a weak alignment pulse. We show that this behavior is a consequence of the spin-rotation and the spin-spin couplings in the triplet ground state of the neutral molecule. A model that includes these couplings in the field-free Hamiltonian but in neither the alignment nor the ionization step explains most of the observed dynamics, suggesting that neither process depends explicitly on the electronic spin. We also show that the angle dependence of strong-field ionization can be retrieved from the delay-dependent signal even when coupling to spin complicates the rotational dynamics.